The shattering peace - Scalzi, John, 1969- (Scalzi, John, 1969- Old man's war novels, 2025)
"For a decade, peace has reigned in interstellar space. A tripartite agreement between the Colonial Union, the Earth, and the alien Conclave has kept the forces of war at bay, even when some would have preferred to return to the fighting and struggle of former times. For now, more sensible heads have prevailed - and have even championed unity. But now, there is a new force that threatens the hard-maintained peace: The Consu, the most advanced intelligent species humans have ever met, are on the cusp of a species-defining civil war. This war is between Consu factions... but nothing the Consu ever do is just about them. The Colonial Union, the Earth and the Conclave have been unwillingly dragged into the conflict, in the most surprising of ways. Gretchen Trujillo is a mid-level diplomat, working in an unimportant part of the Colonial Union bureaucracy. But when she is called to take part in a secret mission involving representatives from every powerful faction in space, what she finds there has the chance to redefine the destinies of humans and aliens alike... or destroy them forever."--Amazon